Examining knowledge of Mpox among primary care physicians in North-Western Nigeria: an online cross-sectional study - Godpower Chinedu Michael; Bukar A. Grema; Hussaini Y. Magaji; Chinyere Nwosu; Taslim O. Lawal; Mohammed B. Usman; Ramatu Abubakar; Fatima A. Falaki; Muttaka Maude; Zainab Abdulkadir; Abdulgafar L. Olawumi; Zainab U. Abdulazeez; et al. (BMC Health Services Research, 2026)
Abstract Background Mpox is a rare but re-emerging zoonotic disease that causes significant morbidity and mortality. As primary care physicians serve as gatekeepers in the healthcare system, it is essential that they be proficient at identifying and coordinating care for suspected Mpox patients. However, there is a scarcity of studies on the knowledge of Mpox among primary care doctors in the northwestern geopolitical zone of Nigeria. Objectives This study assessed the knowledge of Mpox and its associated sociodemographic factors among primary care physicians in northwestern Nigeria. Methods This cross-sectional online study employed a multi-stage sampling technique to survey primary care physicians working in Family Medicine/General Outpatient and Pediatric Outpatient Clinics across hospitals in the seven states of North-Western Nigeria. The minimum sample size of 153 was calculated using an assumed 50% prevalence of good Mpox knowledge, a 5% margin of error, and a 95% confidence level; this was increased to 170 after adding a 10% non-response buffer. A total of 155 physicians completed the survey, giving a completion rate of 91.2%. Data were collected using a pretested, online questionnaire, and descriptive and inferential statistical analyses were done using Epi Info (version 7). Results The mean age of participants was 38.8 ± 7.4 years, with male preponderance (60.7%). Most were general outpatient clinic doctors (77.4%), with ≥ 10 years of practice experience (63.2%), and senior registrars (36.1%). Only 18.9% had prior experience in diagnosing or managing Mpox. Nine (5.8%) had good knowledge of Mpox, with a mean overall knowledge score of 61.7 ± 12.5%. Participants with ≥ 10 years of practice experience ( p = 0.049), senior professional cadres ( p = 0.031), and involvement in diagnosing or managing Mpox ( p = 0.021) were associated with higher mean knowledge scores. Conclusions The overall good knowledge rate was notably low, indicating a significant gap in participants’ knowledge of the various aspects of the disease. Senior professional cadres, long years of practice, and experience in the diagnosis and management of Mpox were associated with higher yet suboptimal knowledge scores. Hence, targeted educational interventions are needed to enhance their preparedness to identify and coordinate Mpox cases in primary care settings.